2013
DOI: 10.1007/s11552-013-9570-1
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Dorsal Wrist Ganglion Excision with Color-Aided Visualization of the Stalk: Minimum 1-Year Follow-Up

Abstract: Background Dorsal wrist ganglia (DWG) are a common, benign soft-tissue mass of the wrist. Excision of DWG is a common procedure performed by hand surgeons and may be performed using either open or arthroscopic techniques. This study aims to evaluate the frequency of stalk visualization with intralesional injection of inert dye in the course of arthroscopic excision along with incidence of recurrence with a minimum of 1-year follow-up. Methods Upon IRB approval, a retrospective chart review was performed identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
(37 reference statements)
0
12
0
1
Order By: Relevance
“…7 Revision of literature shows different recurrence rates of 0% to 11%. 1,13,21,25,30,32,33 In our study, we found recurrence in 1 patient (29%), 3 months following arthroscopic treatment; the patient refused further surgical treatment because he was asymptomatic. We believe that two factors are possibly responsible for the recent excellent success rates of arthroscopic resection of dorsal wrist ganglion: further dissemination of technical knowledge about wrist arthroscopy, and a skill progression of most surgeons in the natural learning curve of the wrist arthroscopy technique.…”
Section: Discussionmentioning
confidence: 50%
“…7 Revision of literature shows different recurrence rates of 0% to 11%. 1,13,21,25,30,32,33 In our study, we found recurrence in 1 patient (29%), 3 months following arthroscopic treatment; the patient refused further surgical treatment because he was asymptomatic. We believe that two factors are possibly responsible for the recent excellent success rates of arthroscopic resection of dorsal wrist ganglion: further dissemination of technical knowledge about wrist arthroscopy, and a skill progression of most surgeons in the natural learning curve of the wrist arthroscopy technique.…”
Section: Discussionmentioning
confidence: 50%
“…Sometimes, the simple puncture of the ganglion made it possible to verify its position by regression of an intra-articular bulge. Other authors, such as Dumontier et al 6 or Ahsan and Yao, 7 injected methylene blue into the ganglion, and the localization was confirmed when the blue spread throughout the joint. Osterman and Raphael 8 and Mathoulin preferred to locate the ganglion using needles introduced in a trans-cystic manner.…”
Section: Methodsmentioning
confidence: 83%
“…One of the authors of the present study uses the technique proposed by Yao and Trindade 13 to facilitate the location of the cyst pedicle. 14 Prior to arthroscopy, the cyst is infiltrated with 2 mL or 3 mL of methylene blue. As such, the whole cyst is tinted by the dye, and intra-articular visualization is made easier.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Um dos autores do presente estudo utiliza a técnica proposta por Yao e Trindade 13 para facilitar a localização do pedículo do cisto. 14 Nela, previamente à artroscopia, infiltra-se o cisto com 2 mL ou 3 mL de azul de metileno. Isso fará com que todo o cisto fique tingido pelo corante, facilitando a visualização intra-articular.…”
Section: Técnica Cirúrgicaunclassified